2020
DOI: 10.3390/foods9081023
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Microstructure Properties of Oyster Mushroom-Soy Protein Meat Analog via Single-Screw Extrusion

Abstract: Single-screw extrusion of a fibrous-structured meat analog from soy proteins added with low-grade oyster mushroom was successful. Satisfactory extrudates were obtained at a barrel temperature of 140 °C, screw speed range of 100–160 rpm, and oyster mushroom addition at 0%, 7.5%, and 15% via factorial experiments. Single-screw extrusion equipped with a slit die successfully produced expanded oyster mushroom-soy protein extrudates. However, the increase in the oyster mushroom content significantly decreased (p ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Figure 2 shows the changes in the air cells and the overall structure of the TVP after different post‐treatments. The control (untreated) (A) sample had many porous structures, including large and small air cells, which were similar to the previously known characteristics of low‐moisture TVP (Mohamad Mazlan et al., 2020). A porous structure was observed in the samples cooked in an oven (C) and the samples heated in a microwave (D), but it was confirmed that the size of the air cells was different from that of the control (A) sample.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Figure 2 shows the changes in the air cells and the overall structure of the TVP after different post‐treatments. The control (untreated) (A) sample had many porous structures, including large and small air cells, which were similar to the previously known characteristics of low‐moisture TVP (Mohamad Mazlan et al., 2020). A porous structure was observed in the samples cooked in an oven (C) and the samples heated in a microwave (D), but it was confirmed that the size of the air cells was different from that of the control (A) sample.…”
Section: Resultssupporting
confidence: 75%
“…The texturization index was determined with a slight modification of the method previously reported by Mohamad Mazlan et al. (2020). Samples were cut into squares (2× 2 cm) and then sheared vertical (lengthwise strength) and parallel (crosswise strength) to 100% of their original height at a rate of 2 mm/s using a Warner–Bratzler stainless steel shear probe.…”
Section: Methodsmentioning
confidence: 99%
“…The trends of plant-protein-based meat analogs have been driven by the combined effects of a growing global population, awareness of the sustainability of animal protein, and societal and environmental concerns. Not only those mentioned but also consumer health considerations on plant protein-based meat analogs that contribute to the health benefits, such as being low in saturated fats and sodium, cholesterol-free, and an excellent source of comparable protein to animal meat [ 1 , 2 , 3 ]. Between 2018 and 2026, the global, Asia-Pacific, and European markets for plant-based meat are anticipated to expand at CAGRs of 14.8, 15.9, and 14.4%, respectively [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different processing techniques, e.g., single screw extrusion [ 1 ], twin-screw extrusion [ 7 , 8 , 9 ], Couette cell technology, shearing, and electrospinning [ 5 ], were applied to develop plant protein-based meat alternatives. The main challenges were the operation to achieve the right texture, appearance, and nutrient content of meat analogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation